Evaluating Emotional and Biological Sensitivity to Maternal Behavior Among Self-Injuring and Depressed Adolescent Girls Using Nonlinear Dynamics. (March 2017) - Crowell, Sheila E.; Butner, Jonathan E.; Wiltshire, Travis J.; Munion, Ascher K.; Yaptangco, Mona; Beauchaine, Theodore P.
High sensitivity and reactivity to behaviors of family members characterize several forms of psychopathology, including self-inflicted injury (SII). We examined mother-daughter behavioral and psychophysiological reactivity during a conflict discussion using nonlinear dynamics to assess asymmetrical associations within time-series data. Depressed, SII, and control adolescents and their mothers participated ( N = 76 dyads). We expected that (a) mothers' evocative behaviors would affect behavioral and psychophysiological reactivity among depressed and, especially, SII adolescents, (b) adolescents' behaviors would not evoke mothers' behavioral or physiological reactivity, and (c) control teens and mothers would be less reactive, with no dynamic associations in either direction. Convergent cross-mapping with dewdrop regression, which identifies directional associations, indicated that mothers' behaviors evoked behavioral responses among depressed and SII participants, but evoked psychophysiological reactivity for SII teens only. There were no effects of adolescents' behavior on mothers' reactivity. Results are interpreted based on sensitivity theories and directions for further research are outlined.